Peptide sequences for sucrose splitting and glucan binding within Streptococcus sobrinus glucosyltransferase (water-insoluble glucan synthetase). - Abo, H (1991)
The gene encoding glucosyltransferase responsible for water-insoluble glucan synthesis (GTF-I) of Streptococcus sobrinus (formerly Streptococcus mutans 6715) was cloned, expressed, and sequenced. A gene bank from S. sobrinus 6715 DNA was constructed in vector pUC18 and screened with anti-GTF-I antibody to detect clones producing GTF-I peptide. Five immunopositive clones were isolated, all of which produced peptides that bound alpha-1,6 glucan. GTF-I activity was found in only two large peptides: one stretching over the full length of the GTF-I peptide and composed of about 1,600 amino acid residues (AB1 clone) and the other lacking about 80 N-terminal residues and about 260 C-terminal residues (AB2 clone). A deletion study of the AB2 clone indicated that specific glucan binding, which is essential for water-insoluble glucan synthesis, was lost prior to sucrase activity with an increase in deletion from the 3' end of the GTF-I gene. These results suggest that the GTF-I peptide consists of three segments: that for sucrose splitting (approximately 1,100 residues), that for glucan binding (approximately 240 residues), and that of unknown function (approximately 260 residues), in order from the N terminus. The primary structure of the GTF-I peptide, deduced by DNA sequencing of the AB1 clone, was found to be very similar to that of the homologous protein from another strain of S. sobrinus.